(untitled) (KYAMC Journal, 2018)
Background: Total thyroidectomy is commonly practice now-a-days for either malignant or benign multinodular goitre. And post-operative hypocalcaemia is a squeal in this operation. Objectives: To find out whether post-operative PTH level is a parameter to identify hypocalcaemia after total thyroidectomy. Materials & Methods: This study was carried out from July 2013 to July 2014 in department of Surgery Sir Salimullah Medical College & Mitford Hospital. Total 116 patients were selected. PTH assay was performed before and after thyroidectomy. 92 patients were undergoing total thyroidectomy and were selected as test group. Rest 24 patients were undergoing unilateral lobectomy and were selected as control group. Serum calcium levels were measured in 1st and 2nd post-operative day. Results: Out of 92 test group patients 31(26.7%) developed postoperative hypocalcemia. Hypocalcemic patients had significantly lower post-operative PTH 5.43 ± 5.32 (median 3.3) compared with that of normocalcemic patient 16.04 ± 11.96 (median 12.5). Serum calcium was significantly lower in hypocalcemic patients at 2nd post-operative day (median 9.8) than in 1st post-operative day (median 10.15). Linear regression curve estimation revealed significant association between post-operative PTH with 2nd post-operative serum calcium. Conclusion: PTH assay can identify patients at risk of clinically significant hypocalcemia much earlier than serum calcium monitoring. A single PTH level post-operatively can reflect early result and help to take necessary measure to avoid hypocalcaemic effect. KYAMC Journal Vol. 9, No.-2, July 2018, Page 43-47